Relative performance information and social comparisons: Exploring managers' cognitive, emotional and dysfunctional behavioral processes. (November 2021) - Carroll, Emma; Marginson, David
Abstract: We explore the cognitive and emotional processes which manifest as a result of social comparisons involving relative performance information. We also explore how and why these processes may invoke dysfunctional behaviors. We mobilize social comparison theory and affective events theory to guide our study. We gather our data from a qualitative field study of a retail organization. Regarding cognitive processes, we find that, faced with a range of relative performance information, managers contemplate and select the most meaningful measurement comparisons for them. Managers also contemplate whether they can influence and attain their selected measures of relative performance. Such contemplation vis-à-vis leaderboard thresholds shape managers' emotions and dysfunctional behaviors. We conclude that perceived control over performance outcomes appears important in understanding how and in what ways social comparison effects unfold. We further conclude that social comparison processes push managers towards continuing performance improvements, even in the context of target achievement. Counterintuitively, perhaps, this effect may not always be organizationally desirable.